Relationships Between Cortically Mediated Attentional Dysfunction and Social Anxiety, Self-Focused Attention, and External Attention Bias. Issue 6 (December 2019) - Tomita, Nozomi; Imai, Shoji; Kanayama, Yusuke; Kumano, Hiroaki
Social anxiety disorder is characterized by a marked fear and avoidance of social situations or a fear of being evaluated by others. Although training for top-down attentional control has been an effective treatment for social anxiety disorder, few studies have demonstrated that individuals with social anxiety have top-down attentional dysfunction. This study used dichotic listening (DL) tasks to investigate the relationship between social anxiety and top-down attentional control over relevant brain activities. We also investigated relationships between both social situation-dependent self-focused attention and external attention bias and situation-independent attentional control. Thirty-six healthy participants underwent near-infrared spectroscopy scanning while performing top-down selective and divided attention DL tasks. Then, they undertook a speech task and completed a questionnaire to assess the degrees of their self-focused attention and external attention bias. The results showed that the degree of social fear and self-focused attention during the speech task were negatively correlated with scores on the selective attention task and with the activity of the left pars opercularis during the selective DL task, which were related to each other. These results suggest that a relationship exists between social fear, self-focused attention in a social situation, and top-down selective attentional dysfunction as assessed both behaviorally and by brain activity changes.